Perencanaan Strategis Penyebaran Tenaga Penjualan Menggunakan Program Dinamik (Studi Kasus: Sentra Kerupuk Lempeng â€œABCâ€) - Noordin Asnawi (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— In making a sale of a product offline usually requires a sales force to market the product to various regions. But in the utilization of sales force, sometimes there are still many who do not plan how to deploy / allocate existing sales force to obtain optimal / maximum and efficient results. Of the various ways, one of the choices of ways that can be used is dynamic programming / programming which is a solution approach, where the method can be used to help provide planning in distributing sales force deployments to several regions, so simply this dynamic program can provide solutions in the problem of distributing the sales force that is done manually by by detailing the problem and solving it in stages. In the case of the distribution of sales force from the "ABC" Plate Crackers Center to several sales areas, the results are obtained for the allocation of sales force to 3 regions (sub-districts) with the result of 0 salespeople for the region (sub-district) 2, 0 salespeople for the region (sub-district) 3, and 3 salespeople for the region (sub-district) 1 in order to obtain maximum / optimal sales results. Keywords—: Sales force; Dynamic Program; Plate crackers.